Zakat Fitri Diuangkan Analisis Nilai Intrekonektif - Dame Siregar (Institut Agama Islam Negeri Padangsidimpuan, 2021)
Based on the existing arguments, zakat fitri can be cashed or local food ingredients. Which is best, which is easy to use, does not make it difficult for the amil, does not harm the devotee and mustahik of zakat. All worship related to food has a choice, namely, freeing the pest, fasting, feeding or clothing. Violating the obligatory pilgrimage to pay hadyu, may be paid with money, the Hajj committee is looking for the animal. The implementation of the Hajj tamattu 'and qiron pays hadyu 1 goat, so that pilgrims are not difficult to find it and pay with money. Pilgrims who are surrounded by headaches have lice, paying hadyu can also be cashed. Hunting halal or haram animals during ihram, pay the amount of the animal being hunted or the price with money. Zakat on various types of trade, then the nisob is calculated all, for 1 haul 354 days, zakat is in the form of money, not every type of sale is issued zakat. Money is a legal medium of exchange, it is easy to carry it, to exchange it. Mustahiq zakat fitri when asked prefers the form of money, even the requester himself prefers alms in the form of money. The phenomenon is that some of the amil, receive zakat fitri in the form of rice, but after buying and selling with worshipers at the mosque. The rice was bought and sold by some of the devotees, finally a lot of money was received. It has not been reviewed yet, the argument for buying and selling at the mosque is whether the rice can be sold by amyl or not. The disadvantage is that all the rice brought by the pemuzkki is expensive, the intermediate is cheap, mixed it all up, in the end it is considered cheap rice.